The kingdom of Kush : handbook of the Napatan-Meroitic civilization - Török, László, 1941- (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1997)
The individual character of Kingdom of Kush has often been overshadowed by the overwhelming cultural presence of its neighbour Egypt. This handbook in our series \'Handbuch der Orientalistik/Handbook of Oriental Studies\' for the first time presents a comprehensive survey of the rich textual, archaeological and art historical evidence for this Middle Nile Region Kingdom of Kush . Basing itself both on the evidence and scholarly literature, this work discusses the emergence of the native state of Kush (after the Pharaonic domination in the 11th century B.C.), the rule of the Kings of Kush in Egypt (c. 760-656) and the intellectual foundations and political history of the Kingdom in the Napatan (7th - Third centuries) and Meroitic (3rd century B.C. - 4th century A.D.) periods.